2020
DOI: 10.1051/0004-6361/202038013
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric study on the temporal variability of the brightness distributions of protoplanetary disks

Abstract: Context. Optical and infrared spatially unresolved multi-epoch observations have revealed the variability of pre-main sequence stars and/or their environment. Moreover, structures in orbital motion around the central star, resulting from planet-disk interaction, are predicted to cause temporal variations in the brightness distributions of protoplanetary disks. Through repeated observations of pre-main sequence stars with the Very Large Telescope Interferometer (VLTI) over nearly two decades, the ESO Archive ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…In contrast, our findings suggest that there is an intrinsic flux variability associated with changes in the morphology of the source. This is in direct line with the results from Kobus et al (2020) et al (2020). The first work uses archival PIONIER data and parametric models applied to the squared visibilities in order to derive morphological changes in the structure of the source.…”
Section: Constraints On the Geometry Of The Targetsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, our findings suggest that there is an intrinsic flux variability associated with changes in the morphology of the source. This is in direct line with the results from Kobus et al (2020) et al (2020). The first work uses archival PIONIER data and parametric models applied to the squared visibilities in order to derive morphological changes in the structure of the source.…”
Section: Constraints On the Geometry Of The Targetsupporting
confidence: 93%
“…In contrast, it also motivates monitoring campaigns to depict the nature of this asymmetry. Additionally, Kobus et al (2020) suggested symmetric variability at sub-au scales based on the relative changes of the squared visibilities observed in PIONIER and AMBER (λ 0 = 2.2 µm) data. However, these analyses do not include the characterization of the closure phases.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, our findings suggest that there is an intrinsic flux variability associated with changes in the morphology of the source. This is in direct line with the results from Kobus et al (2020) who interpret the variability of the squared visibilities for similar baselines at different epochs as changes in the structure of the target. 3.…”
Section: Constraints On the Geometry Of The Targetsupporting
confidence: 90%
“…Asymmetry: we can appreciate that the loci of the brightest side of the Ring model is changing, which strongly supports A97, page 4 of 30 The presence of an asymmetry and hints in the variability have been previously suggested by several authors in the literature. The two most recent are Kobus et al (2020) and Varga et al (2021). The first work uses archival PIO-NIER data and parametric models applied to the squared visibilities in order to derive morphological changes in the structure of the source.…”
Section: Constraints On the Geometry Of The Targetmentioning
confidence: 99%
See 1 more Smart Citation